Electrolyte and battery provided with electrolyte
By integrating a porous insulator with a medium and metal salts in a specific molar ratio to form bridge structures, the electrolyte addresses low ion conductivity, resulting in enhanced ion transport and improved battery performance.
Patent Information
- Application Number
- CN202380037827.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-02
- Filing Date
- 2023-07-21
- Publication Date
- 2024-12-13
AI Technical Summary
Existing electrolytes suffer from low ion conductivity, which hinders efficient ion transport in batteries.
The electrolyte incorporates a porous insulator with micropores containing a medium and metal salts, arranged in a specific molar ratio to form bridge structures that enhance ion conductivity.
The electrolyte achieves significantly improved ion conductivity through the formation of bridge structures, facilitating efficient ion transport and enhancing battery performance.
Smart Images

Figure CN119137781A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrolyte and a battery having the electrolyte. Background Art
[0002] Batteries include air batteries, fuel cells, and secondary batteries, and are used for various purposes. Batteries include a positive electrode and a negative electrode, and an electrolyte that is responsible for ion transport between the positive electrode and the negative electrode.
[0003] For example, Patent Document 1 discloses an ion conductive composite (electrolyte) comprising: an insulating structure composed of a porous coordination polymer having unsaturated sites for metal salt coordination; and a porous coordination polymer composed of [R-SO2-N-SO2-R'] - (R and R' represent fluorine atoms or fluoroalkyl groups); and metal cations (such as Li + 、Na + or Mg 2+ ).
[0004] In addition, Patent Document 2 discloses an electrolyte regulating substance that can be used in metal batteries, comprising a liquid electrolyte and a metal-organic structure (MOF) material that is incorporated into the liquid electrolyte to form a MOF slurry electrolyte. MOF is a cluster of crystalline porous solids constructed by metal cluster nodes and organic connectors, and can bind anions, remove ion pairs, and improve cation transport during activation and infiltration of the liquid electrolyte.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 6222635
[0008] Patent Document 2: Japanese Patent Application No. 2020-508542 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] The present inventors have noticed that the above-mentioned electrolytes still have technical problems to be overcome, and have found that it is necessary to take countermeasures. Specifically, as a technical problem, the present inventors have found that there is room for improvement in the ion conductivity of the electrolyte.
[0011] The present disclosure has been made in view of the above-mentioned technical problems. That is, the main object of the present disclosure is to provide an electrolyte having better ion conductivity than conventional electrolytes.
[0012] Technical solutions for solving technical problems
[0013] The present inventors have attempted to solve the above technical problems by taking measures in a new direction instead of extending the existing technology. As a result, they have completed the invention of an electrolyte that achieves the above main purpose.
[0014] An electrolyte according to one embodiment of the present disclosure includes
[0015] Porous insulator having micropores, and
[0016] The medium and the metal salt are arranged in the micropores,
[0017] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts,
[0018] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 2.0 or less.
[0019] In addition, a battery according to one embodiment of the present disclosure,
[0020] The above-mentioned electrolyte is provided.
[0021] Effects of the Invention
[0022] The present disclosure can provide an electrolyte having better ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a conceptual diagram showing an example of a battery according to the second embodiment of the present disclosure.
[0024] Figure 2 The electrolytes of Examples 1 to 8 and Comparative Examples 1 to 2 have a wavelength of 550 to 600 cm -1 Raman spectrum.
[0025] Figure 3 The electrolytes of Examples 1 to 8 and Comparative Examples 1 to 2 have a wavelength of 680 to 780 cm -1 Raman spectrum.
[0026] Figure 4 It is a graph showing the relationship between the molar ratio (SL / LiFSI) and the ion conductivity at room temperature.
[0027] Figure 5 It is a graph showing the relationship between the molar ratio (EC / LiFSI) and the ion conductivity at room temperature.
[0028] Figure 6 The electrolytes of Examples 23, 25 to 26 and Comparative Example 1 have a wavelength of 870 to 930 cm -1 Raman spectrum.
[0029] Figure 7The electrolytes of Examples 23, 25 to 26 and Comparative Example 1 have a wavelength of 680 to 800 cm -1 Raman spectrum. DETAILED DESCRIPTION
[0030] Hereinafter, the "electrolyte" and the "battery" having the electrolyte of the present disclosure will be described in detail through the embodiments. Although the description is made with reference to the drawings as needed, the contents of the drawings are only schematically and exemplarily shown for the purpose of understanding the present disclosure, and the appearance and dimensional ratios may be different from the actual objects.
[0031] The various numerical ranges mentioned in this specification are intended to include the lower and upper limits themselves, unless otherwise specified, such as "less than," "smaller," and "larger." That is, if a numerical range of 1 to 10 is taken as an example, it is interpreted as including the lower limit 1 and also including the upper limit 10.
[0032] In this specification, "the object part is substantially composed of a specific material" or "the object part is formed of a specific material" means that the object part contains the specific material in a ratio of 95 mass %, 97 mass %, 99 mass %, or 100 mass %. For example, "mesoporous silica is substantially composed of silicon dioxide (SiO2)" means that the mesoporous silica contains silicon dioxide (SiO2) in a ratio of 95 mass %, 97 mass %, 99 mass %, or 100 mass %.
[0033] In the present disclosure, "battery" refers in a broad sense to a device equivalent to 1 or 2 that can extract energy by electrochemical reaction. In a narrow sense, "battery" refers to a device that has a pair of electrodes and an electrolyte, and in particular, is charged and discharged with the movement of ions. Although it is only an example, as a battery, for example, primary batteries and secondary batteries can be listed, more specifically, lithium batteries, magnesium batteries, sodium batteries, and potassium batteries.
[0034] In the present disclosure, unless otherwise specified, the "electrolyte" refers to an electrolyte obtained by removing a porous insulator from the electrolyte involved in the present disclosure, and refers to an electrolyte composed of a metal salt and a dielectric.
[0035] <First embodiment: electrolyte>
[0036] The electrolyte according to the first embodiment of the present disclosure is used in, for example, a battery. That is, the electrolyte described in this specification corresponds to an electrolyte used in a device that can extract energy by electrochemical reaction.
[0037] The electrolyte involved in the first embodiment is, as a premise, an electrolyte for a battery having an electrode composed of lithium, magnesium, sodium or potassium. In particular, it is an electrolyte for a battery having a lithium electrode as a negative electrode. Therefore, the electrolyte involved in the first embodiment can also be said to be an electrolyte for a lithium electrode-based battery (hereinafter, also referred to as a "lithium electrode-based electrolyte").
[0038] Here, the "lithium electrode" used in this specification refers to an electrode having lithium (Li) as an active ingredient (i.e., an active material) in a broad sense. In a narrow sense, a "lithium electrode" refers to an electrode comprising lithium, for example, an electrode comprising lithium metal or a lithium alloy, and in particular, a negative electrode of such lithium. It should be noted that the lithium electrode may contain components other than lithium metal or lithium alloy, but in a preferred embodiment, it is an electrode composed of a metal body of lithium (for example, an electrode composed of a monomer of lithium metal having a purity of 90% or more, preferably a purity of 95% or more, and more preferably a purity of 98% or more).
[0039] The electrolyte according to the first embodiment has Li ion conductivity in the case of a lithium electrode system. The ion conductivity of the electrolyte according to the first embodiment is, for example, 10 -4 The method for measuring the ion conductivity is described in detail in the examples.
[0040] The electrolyte according to the first embodiment includes
[0041] Porous insulator having micropores, and
[0042] The medium (medium molecules) and metal salts are arranged in the micropores.
[0043] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts,
[0044] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 2.0 or less.
[0045] (Molar ratio (medium / metal salt))
[0046] The molar ratio of medium to metal salt (medium / metal salt) is 0.1 or more and 2.0 or less. When the molar ratio is less than 0.1 or greater than 2.0, the ionic conductivity is reduced. From the viewpoint of further improving the ionic conductivity of the electrolyte, the lower limit of the molar ratio is preferably 0.2, more preferably 0.3, and the upper limit of the molar ratio is preferably 1.9, more preferably 1.5, further preferably 1.2, particularly preferably 1.0, and very preferably 0.8. By arbitrarily selecting and combining from the above-mentioned multiple preferred numerical ranges, it is possible to set the preferred numerical range of the molar ratio (including the numerical range of the upper limit and the lower limit). For example, the molar ratio is preferably 0.2 or more and 2.0 or less.
[0047] In particular, the molar ratio (sulfolane / LiFSi) is preferably 0.1 to 1.5, more preferably 0.2 to 1.2, further preferably 0.2 to 1.0, particularly preferably 0.3 to 0.5. In addition, the molar ratio (ethylene carbonate / LiFSi) is preferably 0.2 to 2.0, more preferably 0.3 to 1.0.
[0048] ―Method for determining the molar ratio (medium / metal salt)―
[0049] The molar ratio (medium / metal salt) can be determined by the amount of the medium and metal salt added (molar ratio in the raw material state) constituting the electrolyte involved in this embodiment. Alternatively, the molar ratio (medium / metal salt) can also be determined by the electrolyte (as a finished product).
[0050] [Mechanism of action]
[0051] The electrolyte involved in this embodiment has better ion conductivity. Although not limited to a specific theory, the reasons can be inferred as follows. In the electrolyte involved in this embodiment, the metal salt and the medium can form a bridge structure in a specific molar ratio (medium / metal salt=0.1~2.0). In detail, the electrolyte involved in this embodiment can take at least one of a bridge structure in which the medium and the positive ions (more specifically, metal ions) constituting the metal salt are alternately arranged (hereinafter also referred to as the "first bridge structure"), and a bridge structure in which the positive ions constituting the metal salt and the negative ions constituting the metal salt are alternately arranged (hereinafter also referred to as the "second bridge structure").
[0052] If the first bridge structure and the second bridge structure are arranged in the micropores of the porous insulator, a part of them forms defects (holes) where metal ions are missing, which can become a path for effectively transporting metal ions in the electrolyte. Therefore, in the electrolyte involved in this embodiment, by forming the above-mentioned bridge structure in the micropores of the porous insulator, the ion conductivity of the metal ions becomes higher.
[0053] (The reason for proposing this disclosure)
[0054] When the electrolyte used in lithium-ion batteries is impregnated into a porous insulator, the ion conductivity is still low.
[0055] The inventors of the present invention have conducted in-depth research on the concept of improving the ion conductivity and found that, by forming a bridge structure in the micropore, the metal ions propagate through at least one of the first bridge structure and the second bridge structure in the micropore, and the ion conductivity becomes higher than the mechanism in which only the metal ions propagate in the micropore in a solvated state.
[0056] From this, the present inventors have conceived of an electrolyte according to the present embodiment that improves ion conductivity by a completely new mechanism that does not exist in the conventional concept, that is, carrier transport is performed by at least one of the first bridge structure and the second bridge structure.
[0057] (First bridge structure)
[0058] From the viewpoint of further improving ion conductivity, the electrolyte involved in this embodiment preferably has a first bridge structure. In the first bridge structure, the medium and the positive ions constituting the metal salt are arranged alternately, and a part of the positive ions (metal ions) is missing. The first bridge structure is described in detail with reference to [Chemical Formula 1].
[0059] [Chemical formula 1]
[0060]
[0061] As an example of the electrolyte involved in this embodiment, [Chemical Formula 1] lists a porous insulator containing sulfolane as a medium and metal ions Li + The electrolyte composed of metal salt (sulfolane-Li + In sulfolane-Li + In the electrolyte of the system, in the first bridge structure, the sulfonyl group (oxygen atom) of sulfolane and Li + Coordination, sulfolane and Li + Alternately arranged in one dimension, with a portion of Li + Missing defects (dashed circles in [Chemical Formula 1]). + When the first bridge structure is observed from an angle, in the first bridge structure, the adjacent Li + In addition, due to the presence of Li + defects, so the adjacent Li + can move to the defect via sulfolane. + Since the metal ions can sequentially move in the first bridge structure, it is considered that the first bridge structure contributes to efficient transport of metal ions in the electrolyte, thereby achieving more excellent ion conductivity.
[0062] It should be noted that, in the first bridge structure, the one-dimensional arrangement means that, for example, sulfolane and Li + Arranged in a straight chain. However, sulfolane and Li + The arrangement of is not limited to this. For example, sulfolane and Li + The arrangement may be two-dimensional or three-dimensional, and more specifically, the linear arrangement may be bent or branched.
[0063] (Confirmation method of the first bridge structure)
[0064] The first bridge structure can be confirmed by structural analysis based on Raman spectroscopy. As described above, the first bridge structure can be constructed by the coordination of the metal ions of the metal salt and the medium. That is, the first bridge structure can be constructed by forming a coordination bond between the metal ions and the specific functional groups of the medium. Therefore, by using micro-Raman spectroscopy to confirm that "the peak of the specific vibration of the functional group derived from the coordinated bond is shifted to the high wave number side compared to the peak of the specific vibration of the functional group derived from the uncoordinated state", the existence of the first bridge structure can be confirmed.
[0065] For example, the above-mentioned sulfolane-Li + The existence of the first bridge structure in the electrolyte can be confirmed by using micro-Raman spectroscopy to confirm that "in the Raman spectrum, the peak of the SO2 angular vibration of the sulfonyl group originating from the medium (Raman scattering peak) is shifted to the high wave number side". It can be confirmed by the peak of the angular vibration of O=S=O of the sulfonyl group in the state coordinated with the metal ion being shifted to the high wave number side compared with the peak of the angular vibration of O=S=O of the sulfonyl group in the state not coordinated with the metal ion (known peak).
[0066] In addition, ethylene carbonate-Li + The presence of the first bridge structure in the electrolyte of the system can be confirmed by the shift of the peak of the breathing vibration of the heterocyclic ring derived from the medium (ethylene carbonate) to the high wave number side. + The presence of the first bridge structure in the electrolyte of the system can be confirmed by the shift of the peak of the stretching vibration of the heterocyclic ring derived from the medium (GBL) to the high wave number side.
[0067] The method for confirming the first bridge structure is described in detail in the examples.
[0068] (Second bridge structure)
[0069] From the viewpoint of further improving ion conductivity, the electrolyte involved in this embodiment preferably has a second bridge structure. In the second bridge structure, positive ions constituting the metal salt and negative ions constituting the metal salt are arranged alternately. The second bridge structure is described in detail with reference to [Chemical Formula 2].
[0070] [Chemical formula 2]
[0071]
[0072] As an example of the electrolyte according to the present embodiment, [Chemical Formula 2] lists the electrolyte containing metal ions Li in the micropores of the porous insulator. + and an electrolyte (Li + -FSI electrolyte). In Li + In the electrolyte of the -FSI system, in the second bridge structure, the sulfonyl group (oxygen atom) of the FSI ion and the Li + Coordination, FSI ion and Li + Alternately arranged in one dimension, with a portion of Li + Missing defects (dashed circles in [Chemical Formula 2]). + When the second bridge structure is observed from an angle, in the second bridge structure, the adjacent Li + Through FSI ion bridging. In addition, due to the presence of Li + defects, so the adjacent Li + The FSI ions can move to the defect. + Since the metal ions can sequentially move in the second bridge structure, it is considered that the second bridge structure contributes to efficient transport of metal ions in the electrolyte, thereby achieving more excellent ion conductivity.
[0073] It should be noted that in the second bridge structure, the arrangement in one dimension means that, for example, FSI ions and Li + Arranged in a straight chain. However, FSI ions and Li + The arrangement of FSI ions and Li + The arrangement may be two-dimensional or three-dimensional. More specifically, the linear arrangement may be bent or branched.
[0074] (Method for confirming the second bridge structure)
[0075] The second bridge structure can be confirmed by structural analysis based on Raman spectroscopy. As described above, the second bridge structure can be constructed by the coordination of the metal ion of the metal salt with the negative ion. That is, the second bridge structure can be constructed by forming a coordination bond between the metal ion and the specific functional group of the negative ion. Therefore, by using micro-Raman spectroscopy to confirm that "the peak of the specific vibration of the functional group derived from the coordinated bond is shifted to the high wave number side compared to the peak of the specific vibration of the functional group derived from the uncoordinated state", the existence of the second bridge structure can be confirmed.
[0076] For example, in the above-mentioned metal salt LiFSI, its existence can be confirmed by using micro-Raman spectroscopy to confirm that "in the Raman spectrum, the peak of the SNS stretching vibration originating from the negative ions constituting the metal salt is displaced to the high wave number side". For example, in the case where the negative ions constituting the metal salt are FSI ions, the peak of the stretching vibration of the SNS of the sulfonyl group in the state coordinated with the metal ion is shifted to the high wave number side compared to the peak (known peak) of the stretching vibration of the SNS of the sulfonyl group in the state not coordinated with the metal ion, thereby being able to confirm. The method for confirming the first bridge structure is described in detail in the embodiments.
[0077] The electrolyte according to this embodiment may be a solid electrolyte.
[0078] The electrolyte involved in this embodiment has a porous insulator, a dielectric and a metal salt. The electrolyte involved in this embodiment can further have components other than these components (porous insulator, dielectric and metal salt) within the scope of exerting the main effect of the present disclosure. Below, these components constituting the electrolyte are described.
[0079] (Porous Insulator)
[0080] The porous insulator has a medium and a metal salt disposed in its micropores. Thus, the electrolyte involved in the first embodiment easily forms a first bridge structure and a second bridge structure that contribute to better ion conductivity. The porous insulator has micropores. The porous insulator is, for example, at least one selected from the group consisting of a metal organic structure, a zeolite, and mesoporous silica.
[0081] From the viewpoint of improving the ionic conductivity of the electrolyte, the porous insulator is preferably zeolite and mesoporous silica. Although not limited to a specific theory, it can be inferred that the reason is as follows. In the electrolyte involved in the present embodiment, it can be considered that if the electrolyte contains at least one of zeolite and mesoporous silica (if it is at least one of zeolite and mesoporous silica) as a porous insulator, the silanol group (Si-OH) present in the inner wall of the micropores of the zeolite and mesoporous silica is used as a carrier (positive ions of metal salts, more specifically, Li + More specifically, it is believed that the protons (H + ) is exchanged with the carrier, and the silanol group functions as a hopping site of the carrier. Therefore, when the electrolyte contains at least one of zeolite and mesoporous silica as a porous insulator, the ionic conductivity of the electrolyte is further improved.
[0082] In porous insulators, for zeolites and mesoporous silica, from the viewpoint of improving the ionic conductivity of the electrolyte, the Si / Al ratio is, for example, 5 or more, preferably 15 or more, more preferably 30 or more, further preferably 100 or more, particularly preferably 500 or more, and very particularly preferably 770 or more. In addition, the Si / Al ratio is, for example, 10,000 or less. These upper and lower limits can be arbitrarily combined to form a numerical range (for example, 5 or more and 10,000 or less). In this specification, the Si / Al ratio refers to the molar ratio of Si (silicon atoms) to Al (aluminum atoms) constituting the porous insulator.
[0083] If the Si / Al ratio is 5 or more, the zeolite and mesoporous silica can have more silanol groups on the inner wall of their micropores. This is because it is believed that in this case, more carrier hopping sites can exist on the inner wall of the micropores of the zeolite and mesoporous silica, and the ion conductivity of the electrolyte is further improved.
[0084] The Si / Al ratio of zeolite and mesoporous silica is measured as follows. The zeolite or mesoporous silica is crushed to a degree that can be measured and placed in a nuclear magnetic resonance device ("ECA400 FT-NMR device" manufactured by JEOL Ltd.). At a magnetic field strength of 9.2 T and nuclides: 29 The Si / Al ratio was obtained by measuring the Si content under the conditions specified in the present invention and obtaining an NMR spectrum.
[0085] It should be noted that the zeolite or mesoporous silica used in the measurement of the Si / Al ratio can be measured not only in the raw material state, but also in the state separated from the finished product (for example, the electrolyte or a battery having an electrolyte (more specifically, the measurement unit cell described later in the examples)).
[0086] Commercially available products of metal organic structures include, for example, "UiO-67", "HKUST-1", and "F-free MIL-100 (Fe) (KRICT (trademark) F100)" manufactured by Strem Chemicals, and "ZIF-8 (Basolite (registered trademark)) (Z1200)" and "MIL-53 (Basolite A100)" manufactured by Merck. Commercially available products of zeolite include, for example, "HS-690", "HS-642", and "HS-320" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and "HSZ-360HUA", "HSZ-385HUA", "HSZ-390HUA", "HSZ-660HOA", "HSZ-840HOA", "HSZ-890HOA", and "HSZ-980HOA" manufactured by Tosoh Corporation. Examples of commercially available mesoporous silica include "MCM-41", "MCM-48", "SBA-15" and "SBA-16" manufactured by Sigma Aldrich.
[0087] (medium)
[0088] The medium is an electrically neutral molecule. The medium disperses, dissolves or solid-dissolves the metal salt in the electrolyte. The medium is preferably at least one of a sulfonyl medium, a carbonate medium, an ether medium and a dioxolane medium. Among them, the medium is preferably a carbonate medium.
[0089] The sulfonyl-based mediator is a mediator having a sulfonyl group, and is selected from the group consisting of, for example, sulfolane, dimethyl sulfone, 3-methyl sulfone, and ethyl methyl sulfone.
[0090] The carbonate-based medium is a cyclic carbonate compound (more specifically, a 5-membered ring or 6-membered ring alkylene carbonate compound having 3 to 6 carbon atoms), for example, selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate (fluoroethylene carbonate). The carbonate-based medium may have a halogen group (more specifically, a fluorine group, etc.) and a CC double bond.
[0091] The chain ether-based medium is a compound containing 2 to 4 ether bonds, and is, for example, selected from the group consisting of 1,2-diethoxyethane and diethylene glycol dimethyl ether.
[0092] The lactone-based mediator is a cyclic ester compound (more specifically, a 5-membered or 6-membered ester compound having 4 to 7 carbon atoms), and is selected from the group consisting of, for example, γ-butyrolactone and δ-valerolactone.
[0093] The cyclic ether-based medium is an oxygen-containing heterocyclic compound of a 5-membered ring or a 6-membered ring containing two oxygen atoms as ring members, and is selected from the group consisting of dioxolane (1,3-dioxolane) and dioxane (more specifically, 1,3-dioxane, etc.).
[0094] If the medium is at least one of these, it is easy to form the first bridge structure with the metal ions constituting the metal salt in the electrolyte. Therefore, in this case, the ion conductivity of the electrolyte involved in this embodiment becomes higher.
[0095] (Metal Salt)
[0096] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts. As metal salts, for example, alkali metal salts (more specifically, lithium metal salts, etc.) can be listed. As lithium metal salts, for example, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4) and lithium perchlorate (LiClO4) can be listed. As lithium salts, LiFSI and LiTFSI are preferred, and LiFSI is more preferred. As alkali metal ions constituting alkali metal salts, for example, Li + 、Na + and K + Examples of the alkaline earth metal ions constituting the alkaline earth metal salt include Mg 2+ The metal ion (positive ion) constituting the metal salt is preferably Li + , K + 、Na + or Mg 2+ From the viewpoint of further improving the ionic conductivity of the electrolyte involved in the present embodiment, the negative ions constituting the metal salt are preferably coordinated with the positive ions constituting the metal salt to form a second bridge structure with the positive ions (metal ions) constituting the metal salt. As the negative ions constituting such a metal salt, for example, at least one selected from the group consisting of bis(fluorosulfonyl)imide ions (FSI ions), bis(trifluoromethanesulfonyl)imide ions (TFSI ions), tetrafluoroborate ions, and perchlorate ions.
[0097] (Method for producing electrolyte)
[0098] An example of a method for manufacturing the electrolyte according to the first embodiment is described. The method for manufacturing the electrolyte according to the first embodiment includes: a step of preparing an electrolyte solution including a metal salt and a medium (electrolyte solution preparation step); and a step of impregnating a porous insulator having micropores with the electrolyte solution (impregnation step).
[0099] - Electrolyte preparation process -
[0100] The electrolyte solution preparation step prepares an electrolyte solution including a metal salt and a medium.
[0101] - Impregnation process -
[0102] The impregnation step allows the electrolyte to be impregnated into the porous insulator having micropores. As a result, the micropores of the porous insulator are filled with the electrolyte. When the prepared electrolyte is not a liquid at room temperature (25° C.) (for example, a solid, a quasi-solid (more specifically, a solid mixed in a liquid)), the electrolyte can be heated and impregnated into the porous insulator in a liquid state.
[0103] <Second embodiment: Battery>
[0104] The battery according to the second embodiment includes the electrolyte according to the first embodiment. The battery according to the second embodiment may include a positive electrode and a negative electrode in addition to the electrolyte.
[0105] In the battery according to the present embodiment, the positive electrode includes a material constituting the positive electrode (more specifically, a positive electrode active material, etc.). The negative electrode includes an alkali metal (more specifically, Li, Na, K) or an alkaline earth metal (more specifically, Mg) as a material constituting the negative electrode (specifically, a negative electrode active material). The negative electrode includes, for example, a single body (more specifically, a plate, foil, and layer) of an alkali metal or an alkaline earth metal and a compound thereof.
[0106] The battery according to this embodiment can be configured as a secondary battery. Figure 1 The conceptual diagram of this case is shown. As shown in the figure, during charging, the metal ions (Mn + (M represents a metal element, and n represents a positive integer): More specifically, Li + 、Na + , K + Mg 2+ The metal ions move from the positive electrode 10 to the negative electrode 11 through the electrolyte 12, thereby converting electrical energy into chemical energy and storing electricity. During discharge, the metal ions return from the negative electrode 11 to the positive electrode 10 through the electrolyte 12, thereby generating electrical energy.
[0107] The battery involved in the second embodiment can be used as a driving power source or auxiliary power source for a notebook computer, a PDA (portable information terminal), a mobile phone, a smart phone, a cordless phone, a camcorder, a digital still camera, an electronic book, an electronic dictionary, a portable music player, a radio, a headset, a game console, a navigation system, a memory card, a pacemaker, a hearing aid, an electric tool, an electric shaver, a refrigerator, an air conditioner, a television receiver, a stereo, a water heater, a microwave oven, a dishwasher, a washing machine, a dryer, a lighting device, a toy, a medical device, a robot, a load regulator, a signal light, a railway vehicle, a golf cart, an electric cart and / or an electric vehicle (including a hybrid vehicle), etc. In addition, it can be carried as a power storage power source for a building represented by a residence or a power generation device, or used to supply power to them. In an electric vehicle, a conversion device that converts electric power into a driving force by supplying electric power is generally a motor. As a control device (control unit) for performing information processing related to vehicle control, a control device for displaying the remaining battery amount based on information related to the remaining battery amount is included. In addition, the battery can also be used as a power storage device in a so-called smart grid. Such a power storage device can not only supply power, but also store power by receiving power from other power sources. As other power sources, for example, thermal power generation, nuclear power generation, hydropower generation, solar cells, wind power generation, geothermal power generation and / or fuel cells (including biofuel cells) can be used.
[0108] Although the embodiments of the present disclosure have been described above, these are merely typical examples, and therefore, the present disclosure is not limited thereto, and it is easily understood by those skilled in the art that various embodiments can be considered without changing the gist of the present disclosure.
[0109] For example, the composition of the electrolyte, the raw materials used in the manufacture, the manufacturing method, the manufacturing conditions, the characteristics of the electrolyte, the structure or construction of the battery are illustrative, not limited to these, and can be appropriately changed. For example, as a battery, in addition to a lithium battery, a magnesium battery, a sodium battery, and a potassium battery, an air battery and a fuel cell can also be listed.
[0110] Example
[0111] Hereinafter, the present disclosure will be described in more detail using examples, but the present disclosure is not limited to these examples.
[0112] <Example 1>
[0113] [1-1. Preparation of electrolyte]
[0114] (1-1. Raw materials)
[0115] The following raw materials were used.
[0116] -Porous insulators: Metal-organic frameworks (MOFs)-
[0117] Strem Chemicals' "UiO-67": MOF represented by Zr6O4(OH)4(BPDC)6 (BPDC: biphenyl dicarboxylate)
[0118] ·Strem Chemicals' "HKUST-1": MOF composed of Cu and 1,3,5-benzenetricarboxylic acid
[0119] · Merck "ZIF-8 (Basolite (Z1200) (trademark))": Zeolite-imidazole salt structure (ZIF): MOF composed of Zn and 2-methylimidazole
[0120] Strem Chemicals' "F-free MIL-100(Fe)(KRICT(trademark) F100)": Fe3(O)(OH)(C9H3O6)2: (MOF composed of Fe and 1,3,5-benzenetricarboxylic acid)
[0121] ·MIL-53 (Basolite A100) manufactured by MERCK: Al(OH)C8H4O4
[0122] - Porous insulator: Zeolite -
[0123] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-320" (crystal system: Y-type, Si / Al ratio = 5.5, cationic species: H; hereinafter also referred to as "HS-320 (H)")
[0124] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-320" (crystal system: Y-type, Si / Al ratio = 5.5, cationic species: Na; hereinafter also referred to as "HS-320 (Na)")
[0125] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-642" (crystal system: mordenite, Si / Al ratio = 18, cation species: Na)
[0126] Fujifilm Wako Pure Chemical Industries, Ltd. "HS-690" (crystal system: mordenite, Si / Al ratio = 180, cationic species: H)
[0127] · Tosoh Corporation "HSZ-360HUA" (crystal system: Y type, Si / Al ratio = 15, cationic species: H)
[0128] · Tosoh Corporation "HSZ-385HUA" (crystal system: Y type, Si / Al ratio = 100, cationic species: H)
[0129] · Tosoh Corporation "HSZ-390HUA" (crystal system: Y type, Si / Al ratio = 770, cationic species: H)
[0130] · "HSZ-660HOA" manufactured by Tosoh Corporation (crystal system: mordenite, Si / Al ratio = 30, cation species: H)
[0131] · "HSZ-840HOA" manufactured by Tosoh Corporation (crystal system: ZSM-5, Si / Al ratio = 40, cation species: H)
[0132] · Tosoh Corporation "HSZ-980HOA" (crystal system: beta, Si / Al ratio = 500, cationic species: H)
[0133] - Porous insulator: mesoporous silica -
[0134] · "MCM-41" manufactured by Sigma-Aldrich
[0135] · "MCM-48" manufactured by Sigma-Aldrich
[0136] · "SBA-15" manufactured by Sigma-Aldrich
[0137] · "SBA-16" manufactured by Sigma-Aldrich
[0138] It should be noted that these four types of mesoporous silica do not contain Al artificially and are substantially composed of silicon dioxide (SiO 2 ). Therefore, it can be considered that the Si / Al ratio of these mesoporous silicas is at least greater than 10,000.
[0139] -Metal Salts-
[0140] Lithium bis(fluorosulfonyl)imide (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiFSI")
[0141] Lithium bis(trifluoromethanesulfonyl)imide (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiTFSI")
[0142] Lithium hexafluorophosphate (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiPF6" or "LiPF6")
[0143] Lithium tetrafluoroborate (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiBF4" or "LiBF4")
[0144] Lithium perchlorate (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "LiClO4" or "LiClO4")
[0145] - Medium: Sulfonyl-based medium -
[0146] Sulfolane (manufactured by Kishida Chemical Co., Ltd. (for LBG); hereinafter also referred to as "SL")
[0147] Dimethyl sulfone (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter also referred to as "DMSO2")
[0148] 3-Methylsulfolane (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter also referred to as "MSL")
[0149] Ethyl methyl sulfone (manufactured by Tokyo Chemical Industry Co., Ltd.; hereinafter also referred to as "EMS")
[0150] - Medium: Carbonate-based medium -
[0151] Propylene carbonate (manufactured by Kishida Chemical Co., Ltd.; hereinafter also referred to as "PC")
[0152] Ethylene carbonate (manufactured by Kishida Chemical Co., Ltd.; hereinafter also referred to as "EC")
[0153] Vinylene carbonate (manufactured by Kishida Chemical Co., Ltd.; hereinafter also referred to as "VC")
[0154] Fluoroethylene carbonate (fluoroethylene carbonate) (manufactured by Kishida Chemical Co., Ltd.; hereinafter also referred to as "FEC")
[0155] - Medium: Lactone medium -
[0156] γ-Butyrolactone (manufactured by Kishida Chemical Co., Ltd.; hereinafter also referred to as "GBL")
[0157] - Medium: Chain ether medium -
[0158] ·Diethylene glycol dimethyl ether (manufactured by Kishida Chemical Co., Ltd.)
[0159] 1,2-Dimethoxyethane (manufactured by Kishida Chemical Co., Ltd.; hereinafter also referred to as "DME")
[0160] (1-2. Preparation of solid electrolyte)
[0161] LiFSI as a metal salt and sulfolane SL as a medium were mixed at a molar ratio (medium / metal salt) = 2.0 to prepare an electrolyte solution.
[0162] UiO-67, a porous insulator, is dried under vacuum at 250°C. The prepared electrolyte is impregnated into the dried UiO-67 so that the electrolyte is inserted into and filled in the micropores of UiO-67. A powdered solid electrolyte is thus prepared. The impregnation treatment is performed by mixing the electrolyte and the porous insulator by hand using a mortar and pestle. The impregnation amount (volume) of the electrolyte is set to an amount that is 100% relative to the micropore volume of the porous insulator (UiO-67) measured in advance.
[0163] The preparation of solid electrolytes was carried out in a glove box under argon atmosphere.
[0164] (1-3. Fabrication of measurement unit cell)
[0165] The prepared powdered solid electrolyte was punched at 200 MPa using a uniaxial press ("CDM-20PA" manufactured by Riken Machinery Co., Ltd.). As a stamping die during stamping, a PET resin mold with upper and lower punches was used. In detail, the PET resin mold has a cylindrical shape and has a cylindrical through-opening along the center axis. The punch has a cylindrical shape and is configured to be plugged in and out of the through-opening of the mold, and is configured so that the front end faces (surfaces perpendicular to the insertion direction) of the upper and lower punches are opposed. The powdered solid electrolyte is arranged in the through-opening of the mold in a manner clamped by the front end faces of the upper and lower punches. The upper and lower punches are punched using a uniaxial press, thereby molding the solid electrolyte. In addition, a measuring unit (a unit for measuring) is made by directly using the upper punch and the lower punch of the PET resin mold as blocking electrodes.
[0166] It should be noted that the process of manufacturing the measurement cell was performed in a glove box in an argon atmosphere.
[0167] [2. Measurement method and evaluation method]
[0168] (2-1. Form of electrolyte)
[0169] The appearance of the electrolyte (electrolyte composed of a metal salt and a medium) obtained in the preparation process of the solid electrolyte was visually observed. In addition, the container containing the electrolyte was tilted and the behavior of the liquid level changing parallel to the horizontal plane was visually observed. Based on these observations, the following evaluation criteria were used for determination.
[0170] (Evaluation Criteria)
[0171] Liquid: It has a liquid appearance and is not mixed with solids. When a cylindrical container containing an electrolyte is tilted so that the bottom of the container is 30 degrees to the horizontal plane, the liquid surface of the electrolyte becomes parallel to the horizontal plane in less than 1 second from the start of tilting.
[0172] Sherbet-like: The appearance is a mixture of liquid and solid, and when a cylindrical container containing an electrolyte is tilted so that the bottom of the container is 30 degrees to a horizontal plane, the shape of the liquid surface of the electrolyte changes within a period of more than 1 second and less than 60 seconds after the tilt.
[0173] Solid: Solid in appearance, and when a cylindrical container containing an electrolyte is tilted so that the bottom of the container is 30 degrees to a horizontal plane, the liquid level of the electrolyte does not change even if more than 10 minutes have passed since the tilting.
[0174] (2-2. Measurement of ion conductivity)
[0175] - Preparation of test samples -
[0176] The measurement cell cell produced in (1-3. Production of measurement cell) was sealed in the laminate with tab electrodes to prepare an ion conductivity measurement cell as a measurement sample.
[0177] - Determination of ionic conductivity -
[0178] The ionic conductivity of the sample was measured using an impedance meter (VMP3 manufactured by Biologic). The ionic conductivity was measured using an AC impedance method at room temperature (25°C). The molar ratio (SL / LiFSI) of the solid electrolyte of Example 1 was 2.0, and the ionic conductivity was 1.9×10 -4 (S / cm). The results are shown in Table 1 together with the results of the above-mentioned observation of the appearance of the electrolyte solution. Table 1 shows the molar ratio (SL / LiFSI), the state of the electrolyte solution at room temperature, and the ion conductivity at room temperature.
[0179] (2-3. Structural analysis of electrolytes based on Raman spectroscopy)
[0180] The electrolytes of Example 1 and Examples 2 to 8 described later and Comparative Examples 1 and 2 were subjected to structural analysis using Raman spectroscopy.
[0181] The solid electrolyte formed in (1-3. Preparation of the measuring unit) is used as a measuring sample for structural analysis. The obtained measuring sample is set in a microscopic laser Raman spectrometer ("LabRam HREvolution" manufactured by Horiba, Ltd.). The surface of the measuring sample is irradiated with an infrared laser (wavelength 1064nm), and the Raman spectrum is measured using an objective lens with a spot diameter of 7μm. It should be noted that the Raman spectrum can be measured by irradiating the cut surface formed by cutting the measuring sample (solid electrolyte) for structural analysis with an infrared laser.
[0182] Figure 2 The 550 to 600 cm-1 values of the electrolytes of Examples 1 to 8 and Comparative Examples 1 to 2 are shown. -1 Raman spectrum of Figure 2 In the Raman spectrum shown, the vertical axis represents the Raman intensity (unit: arbitrary intensity) and the horizontal axis represents the Raman shift (unit: cm -1 ). Figure 2 The Raman spectrum shown is at 580-590 cm -1 This peak is at 560-570cm, which is attributed to the SO2 shear vibration (OSO angle vibration) of the sulfonyl group derived from sulfolane. -1 A peak whose nearby peaks are shifted to the high wavenumber side.
[0183] Figure 3 The 680-780 cm-1 of the electrolytes of Examples 1 to 8 and Comparative Examples 1 to 2 are shown. -1 Raman spectrum of Figure 3 In the Raman spectrum shown, the vertical axis represents the Raman intensity (unit: arbitrary intensity) and the horizontal axis represents the Raman shift (unit: cm -1 ). Figure 3 The Raman spectrum shown has a wavelength of 740-750 cm -1 Nearby peaks and 680~690cm -1 Nearby peaks. 740~750cm -1 The peaks near the FSI anion are at 720-740 cm -1 A peak whose nearby peaks are shifted to the high wavenumber side.
[0184] (2-4. Determination of Si / Al ratio by nuclear magnetic resonance method)
[0185] In some of the systems (Examples 41 to 46) using zeolite or mesoporous silica as the porous insulator, the Si / Al ratio of the zeolite or mesoporous silica was determined.
[0186] Specifically, the zeolite or mesoporous silica is crushed to a degree that can be measured. The crushed zeolite or mesoporous silica is placed in a nuclear magnetic resonance device ("ECA400 FT-NMR device" manufactured by JEOL Ltd.). At a magnetic field strength of 9.2 T and nuclides: 29 The measurement was carried out under the conditions of Si measurement, and the result was 29 Si NMR spectrum. 29 The peak area intensity ratio of the Si NMR spectrum yields the Si / Al ratio.
[0187] <Examples 2 to 8 and Comparative Examples 1 and 2: molar ratio>
[0188] The electrolyte was prepared in the same manner as in Example 1, except that the molar ratio (SL / LiFSI) was changed from 2.0 to the molar ratio described in Table 1, and the ion conductivity was measured. In addition, the appearance of the electrolyte solution obtained in the electrolyte preparation step was also observed. These results are shown in Table 1.
[0189] It should be noted that, when the concentration of the metal salt in the electrolyte composed of the metal salt and the medium is relatively high (i.e., when the concentration of the medium is relatively low), the electrolyte sometimes becomes a solid or a liquid with solid precipitated at room temperature (25°C). In this case, the electrolyte is heated until the solid in the prepared electrolyte is completely dissolved (e.g., 100°C), and the infiltration treatment is performed after the liquid is formed.
[0190] In Example 6, a Li4Ti5O 12 A lithium ion secondary battery with LiFePO4 as the positive electrode was charged and discharged at a current of 0.2C (coulomb). The charge and discharge potential was about 1.8V.
[0191] [Results: Examples 1 to 8 and Comparative Examples 1 to 2: molar ratio]
[0192] (Ionic conductivity)
[0193] Table 1 shows the molar ratio (SL / LiFSI) and the ion conductivity at room temperature. Figure 4 . Figure 4 The relationship between the molar ratio (SL / LiFSI) and the ion conductivity at room temperature is shown. Figure 4 The horizontal axis represents the molar ratio, and the vertical axis represents the ionic conductivity at room temperature (unit: S / cm). Figure 4 For example, 1.0E-03 in the record on the vertical axis means 1.0×10-3.
[0194] [Table 1]
[0195]
[0196] *1: Sulfolane *2: Lithium bis(fluorosulfonyl)imide
[0197] In the SL-LiFSI electrolyte, Figure 4 As shown, as the molar ratio (SL / LiFSI) increases from 0.1 to 0.3, the ionic conductivity at room temperature simply increases, as the molar ratio (SL / LiFSI) increases from 0.3 to 2.6, the ionic conductivity at room temperature simply decreases, and as the molar ratio (SL / LiFSI) increases from 2.6 to 9.6, the ionic conductivity at room temperature is approximately the same value.
[0198] In addition, the ionic conductivity of the electrolyte solution composed of SL and LiFSI in Example 4 was measured and the result was below the measurement lower limit (or below the measurement limit; more specifically, about 10 -7 S / cm or less). This is a value equivalent to the ion conductivity of an insulator.
[0199] (First bridge structure)
[0200] In the SL-LiFSI electrolyte, Figure 2 As shown in Figure 2, the peak (Raman scattering peak) derived from the angular vibration of OSO is located at 560-570 cm-1 when the molar ratio (SL / LiFSI) is 2.6-9.6. -1 When the molar ratio (SL / LiFSI) is reduced to 0.5-2.0, it is located at 580-590 cm -1 In the electrolytes of Examples 1 to 5, the peak derived from the angular vibration of OSO is shifted to the high wave number side, compared with the electrolytes of Comparative Examples 1 and 2.
[0201] Based on these results, it can be considered that in the electrolytes of Examples 1 to 8, Li + The first bridge structure is formed with SL as a medium. It can be inferred that the first bridge structure is based on a specific molar ratio (SL / LiFSI).
[0202] (Second bridge structure)
[0203] In the SL-LiFSI electrolyte, Figure 3 As shown in Figure 2, the peak (Raman scattering peak) derived from the stretching vibration of SNS is located at 720-740 cm-1 when the molar ratio (SL / LiFSI) is 2.6-9.6. -1 When the molar ratio (SL / LiFSI) is reduced to 0.5-2.0, it is located at 740-760 cm -1 In the electrolytes of Examples 1 to 5, compared with the electrolytes of Comparative Examples 1 to 2, the peak derived from the SNS stretching vibration gradually shifts to the high wave number side as the molar ratio (SL / LiFSI) decreases.
[0204] Based on these results, it can be considered that in the electrolytes of Examples 1 to 5, the positive ions Li + The negative ion FSI forms a second bridge structure. It can be inferred that the second bridge structure is based on a specific molar ratio (SL / LiFSI).
[0205] [Comparison between Examples 1 to 8 and Comparative Examples 1 to 2]
[0206] The electrolytes of Examples 1 to 8 include UiO-67 as a porous insulator having micropores, SL as a medium having a sulfonyl group arranged in the micropores, and LiFSI as a metal salt, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 1 to 8 are electrolytes included in the scope of the invention of claim 1.
[0207] The ionic conductivity of the electrolytes of Examples 1 to 8 is 1.9×10 -4 ~10.1×10 -4 S / cm.
[0208] The electrolytes of Comparative Examples 1 and 2 are electrolytes not included in the scope of the invention according to claim 1. Specifically, in the electrolytes of Comparative Examples 1 and 2, the molar ratio of the medium to the metal salt (medium / metal salt) exceeds 2.0.
[0209] The ion conductivity of the electrolytes of Comparative Examples 1 and 2 was 1.2×10 -4 S / cm.
[0210] Examples 1 to 8 included in the scope of the invention according to claim 1 have higher ion conductivity at normal temperature (room temperature) than Comparative Examples 1 to 2 not included in the scope of the invention according to claim 1. This shows that the invention according to claim 1 is excellent in ion conductivity.
[0211] <Examples 9 to 14 and Comparative Examples 3 to 5: Porous Insulators>
[0212] An electrolyte was prepared and a battery was fabricated in the same manner as in Example 1 except that UiO-67 as a porous insulator and the molar ratio (medium / metal salt) were changed to the porous insulator (metal organic insulator) and the molar ratio described in Table 2, respectively.
[0213] In addition, the ion conductivity was measured in the same manner as in Example 1. Table 2 shows the results.
[0214] [Table 2]
[0215]
[0216] *1: Sulfolane, *2: Lithium bis(fluorosulfonyl)imide
[0217] [Comparison between Examples 9 to 14 and Comparative Examples 3 to 5]
[0218] The electrolytes of Examples 9 to 14 include any one of HKUST-1, ZIF-8, and MIL-100 (Fe) as porous insulators (metal organic structures) having micropores, and SL as a medium having a sulfonyl group disposed in the micropores, and LiFSI as a metal salt, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 9 to 14 are electrolytes included in the scope of the invention of claim 1.
[0219] The ion transmission rate of the electrolytes of Examples 9 to 14 at room temperature is 2.2×10 -4 ~4.3×10 -4 S / cm.
[0220] The electrolytes of Comparative Examples 3 to 5 are electrolytes not included in the scope of the invention according to claim 1. Specifically, in the electrolytes of Comparative Examples 3 to 5, the molar ratio of the medium to the metal salt (medium / metal salt) exceeds 2.0.
[0221] The ionic conductivity of the electrolytes of Comparative Examples 3 to 5 was 0.77×10 -4 ~1.7×10 -4 S / cm.
[0222] Examples 9 to 14 included in the scope of the invention according to claim 1 have higher ion conductivity at normal temperature (room temperature) than Comparative Examples 3 to 5 not included in the scope of the invention according to claim 1. This shows that the invention according to claim 1 is excellent in ion conductivity.
[0223] <Examples 15 to 20: Metal salt and medium>
[0224] An electrolyte was prepared in the same manner as in Example 1, and a battery was produced, except that LiFSI as the metal salt, SL as the medium, and the molar ratio were changed to the metal salt, medium, and molar ratio (medium / metal salt) described in Table 3, respectively.
[0225] In addition, the ion conductivity was measured in the same manner as in Example 1. Table 3 shows the results.
[0226] [Table 3]
[0227]
[0228] *1: Bis(trifluoromethanesulfonyl)imide, *2: Lithium tetrafluoroborate, *3: Lithium perchlorate,
[0229] *4: Lithium bis(fluorosulfonyl)imide, *5: Sulfolane, *6: Dimethyl sulfone, *7: 3-methylsulfolane,
[0230] *8: Ethyl methyl sulfone
[0231] The electrolytes of Examples 15 to 20 include UiO-67 as a porous insulator having micropores, and any one of SL, DMSO2, MSL and EMS as a medium having a sulfonyl group arranged in the micropores, and LiTFSI, LiBF4, LiClO4 and LiFSI as metal salts, wherein the metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 15 to 20 are electrolytes included in the scope of the invention involved in claim 1.
[0232] The ionic conductivity of the electrolytes of Examples 15 to 20 is 2.7×10 -4 ~3.5×10 -4 S / cm.
[0233] <Examples 21 to 28 and Comparative Examples 6 to 7: EC-LiFSI / UiO-67 System>
[0234] (Ionic conductivity)
[0235] The electrolytes of Examples 21 to 28 were prepared in the same manner as in Example 1, except that the medium was changed from sulfolane (SL) to ethylene carbonate (EC) (manufactured by Kishida Chemical Co., Ltd.) and the molar ratio (EC / LiFSI) described in Table 4 was used, and the ion conductivity was measured. In addition, the appearance of the electrolyte obtained in the preparation process of the electrolyte was also observed. These results are shown in Table 4.
[0236] [Table 4]
[0237]
[0238] *1: Ethylene carbonate, *2: Lithium bis(fluorosulfonyl)imide,
[0239] *3: Electrolyte consisting of metal salt and medium used in each example
[0240] Table 4 shows the molar ratio (EC / LiFSI) and the ion conductivity at room temperature. Figure 5 . Figure 5 The relationship between the molar ratio (EC / LiFSI) and the ionic conductivity at room temperature is shown. In the electrolyte of EC-LiFSI system, Figure 5As shown, as the molar ratio (EC / LiFSI) increases from 0.1 to 0.5, the ionic conductivity at room temperature simply increases, as the molar ratio (EC / LiFSI) increases from 0.5 to 4.0, the ionic conductivity at room temperature simply decreases, and as the molar ratio (EC / LiFSI) increases from 4.0 to 10.0, the ionic conductivity at room temperature is approximately the same value.
[0241] The electrolytes of Examples 21 to 28 include UiO-67 as a porous insulator having micropores, EC as a medium and LiFSI as a metal salt arranged in the micropores, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 21 to 28 are electrolytes included in the scope of the invention of claim 1.
[0242] The ionic conductivity of the electrolytes of Examples 21 to 28 was 3.7×10 -4 ~10×10 -4 S / cm.
[0243] The electrolytes of Comparative Examples 6 and 7 are electrolytes not included in the scope of the invention according to claim 1. Specifically, in the electrolytes of Comparative Examples 6 and 7, the molar ratio of the medium to the metal salt (medium / metal salt) exceeds 2.0.
[0244] The ionic conductivity of the electrolytes of Comparative Examples 6 and 7 was 2.7×10 -4 ~2.9×10 -4 S / cm.
[0245] Examples 21 to 28 included in the scope of the invention according to claim 1 have higher ion conductivity at room temperature than Comparative Examples 6 to 7 not included in the scope of the invention according to claim 1. Therefore, it is clear that the invention according to claim 1 is excellent in ion conductivity.
[0246] in addition, Figure 5 The integral value of the graph showing ionic conductivity is Figure 4 The integral value of the graph showing ion conductivity is large. It can be seen from this that the electrolytes of Examples 21 to 28 show higher ion conductivity than the electrolytes of Examples 1 to 8 (that is, the electrolytes of the EC-LiSFI system have higher ion conductivity than the electrolytes of the SL-LiSFI system).
[0247] (Structural analysis based on Raman spectroscopy)
[0248] - First bridge structure -
[0249] In addition, regarding the electrolytes of Examples 23, 25 to 26 and Comparative Example 6, structural analysis of the electrolytes was performed by Raman spectroscopy in the same manner as in Example 1. Figure 6 The electrolytes of Examples 23, 25 to 26 and Comparative Example 6 have a wavelength of 870 to 930 cm -1 Raman spectrum of Figure 6 In the Raman spectrum shown, the vertical axis represents the Raman intensity (unit: arbitrary intensity) and the horizontal axis represents the Raman shift (unit: cm -1 ). Figure 6 The Raman spectrum shown is between 900 and 910 cm -1 This peak is attributed to the ring breathing vibration (heterocyclic breathing vibration) of ethylene carbonate (EC) at 895 cm -1 A peak whose nearby peaks are shifted to the high wavenumber side.
[0250] In the electrolyte of EC-LiFSI system, Figure 6 As shown, when the molar ratio (EC / LiFSI) is 0.3 to 1.0 (Examples 23, 25 to 26), the peak (Raman scattering peak) derived from the breathing vibration of the heterocyclic ring of EC mainly exists at 900 to 910 cm -1 That is, in the electrolytes of Examples 23, 25 and 26, a peak derived from the breathing vibration was observed to be shifted to a higher wave number side.
[0251] On the other hand, when the molar ratio (EC / LiFSI) is 10 (Comparative Example 6), there are two peaks derived from the respiratory vibration, which are located at 895 cm -1 Nearby and 900~910cm -1 (Shoulder peak) That is, in the electrolyte of Comparative Example 6, a peak derived from the breathing vibration was mainly observed, and a peak slightly shifted to the high wave number side was observed.
[0252] Depend on Figure 6 The results show that it can be considered that in the electrolytes of Examples 23, 25 to 26, the Li + The first bridge structure is formed with EC as a medium. In addition, it is estimated that the bridge structure is based on the molar ratio (EC / LiFSI).
[0253] - Second bridge structure -
[0254] in addition, Figure 7 The 680 to 800 cm-1 values of the electrolytes of Examples 23, 25 to 26 and Comparative Example 6 are shown in FIG. -1 Raman spectrum of Figure 7 In the Raman spectrum shown, the vertical axis represents the Raman intensity (unit: arbitrary intensity) and the horizontal axis represents the Raman shift (unit: cm -1 ). Figure 7The Raman spectrum shown is between 740 and 760 cm -1 This peak is attributed to the SNS stretching vibration of the FSI anion and is located at 710-740cm -1 A peak whose nearby peaks are shifted to the high wavenumber side.
[0255] In the electrolyte of EC-LiFSI system, Figure 7 As shown, the peak (Raman scattering peak) derived from the SNS stretching vibration of the FSI anion mainly has a peak that is shifted to the high wave number side when the molar ratio (EC / LiFSI) is 0.3 to 1.0 (Examples 23, 25 to 26). That is, the electrolytes of Examples 23, 25 to 26 mainly observe peaks that are shifted to the high wave number side due to the angular vibration.
[0256] In contrast, the peak derived from the stretching vibration mainly existed when the molar ratio (EC / LiFSI) was 10 (Comparative Example 6). That is, in the electrolyte of Comparative Example 6, the peak derived from the breathing vibration was mainly observed.
[0257] Depend on Figure 7 The results show that in the electrolytes of Examples 23, 25-26, Li + The second bridge structure is formed with the FSI anion. In addition, the second bridge structure is estimated based on the molar ratio (EC / LiFSI).
[0258] <Examples 29 to 32: EC-LiFSI / MOF system>
[0259] Except that sulfolane (SL) as a medium was changed to ethylene carbonate (EC) (manufactured by Kishida Chemical Co., Ltd.), the molar ratio (SL / LiSFI) was changed to the molar ratio (EC / LiFSI) described in Table 5, and UiO-67 as a porous insulator was changed to the metal organic structure (MOF) described in Table 5, the electrolytes of Examples 29 to 32 were prepared in the same manner as in Example 1, and the ion conductivity was measured. The results are shown in Table 5.
[0260] [Table 5]
[0261]
[0262] *1: Ethylene carbonate, *2: Lithium bis(fluorosulfonyl)imide
[0263] The electrolytes of Examples 29 to 32 include any one of HKUST-1, ZIF-8, MIL-100 (Fe) and MIL-53 as porous insulators (metal organic structures) having micropores, and EC as a medium and LiFSI as a metal salt arranged in the micropores, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 29 to 32 are electrolytes included in the scope of the invention involved in claim 1.
[0264] <Examples 33 to 40 and Comparative Examples 8 to 9: EC-LiFSI / Zeolite System>
[0265] Except that sulfolane (SL) as a medium was changed to ethylene carbonate (EC) (manufactured by Kishida Chemical Co., Ltd.), the molar ratio (SL / LiSFI) was changed to the molar ratio (EC / LiFSI) described in Table 6, UiO-67 as a porous insulator was changed to HS-690 as a zeolite, and the drying temperature of the porous insulator under vacuum was changed from 250°C to 300°C. The electrolytes of Examples 33 to 40 and Comparative Examples 8 to 9 were prepared in the same manner as in Example 1, and the ion conductivity was measured. In addition, the appearance of the electrolyte obtained in the preparation process of the electrolyte was also observed. Their results are shown in Table 6.
[0266] [Table 6]
[0267]
[0268] *1: Ethylene carbonate, *2: Lithium bis(fluorosulfonyl)imide,
[0269] *3: Electrolyte consisting of metal salt and medium used in each example
[0270] The electrolytes of Examples 33 to 40 include HS-690 as a porous insulator (zeolite) having micropores, EC as a medium configured in the micropores, and LiFSI as a metal salt, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 29 to 32 are electrolytes included in the scope of the invention of claim 1.
[0271] The ionic conductivity of the electrolytes of Examples 33 to 40 was 9.7×10 -4 ~54×10 -4 S / cm.
[0272] The electrolytes of Comparative Examples 8 and 9 are electrolytes not included in the scope of the invention according to claim 1. Specifically, the molar ratio of the medium to the metal salt (medium / metal ratio) of the electrolytes of Comparative Examples 8 and 9 exceeds 2.0.
[0273] The ionic conductivity of the electrolytes of Comparative Examples 8 to 9 was 2.5×10 -4 ~2.8×10 -4 S / cm.
[0274] Examples 33 to 40 included in the scope of the invention according to claim 1 have higher ion conductivity at room temperature than Comparative Examples 8 to 9 not included in the scope of the invention according to claim 1 .
[0275] In addition, the electrolyte was changed to the electrolyte of Example 37, Li4Ti5O 12 The battery of Example 37 was produced in the same manner as the battery of Example 1 (battery for measuring ion conductivity), except that LiFePO4 was used as the positive electrode as the negative electrode. The battery of Example 37 thus obtained was charged and discharged at a current of 0.1 C. It was found that the battery of Example 37 was a battery capable of being charged and discharged at about 1.8 V.
[0276] <Examples 41 to 44: EC-LiFSI / zeolite system>
[0277] Except that sulfolane (SL) as a medium was changed to ethylene carbonate (EC) (manufactured by Kishida Chemical Co., Ltd.), the molar ratio (SL / LiSFI) was changed to the molar ratio (EC / LiFSI) described in Table 7, and UiO-67 as a porous insulator was changed to zeolite (any one of HS-320 (H), HSZ-360HUA, HSZ-660HOA, HSZ-385HUA, HSZ-980HOA and HSZ-390HUA), the electrolytes of Examples 41 to 46 were prepared in the same manner as in Example 1, and the ion conductivity was measured. These results are shown in Table 7.
[0278] [Table 7]
[0279]
[0280] *1: Ethylene carbonate, *2: Lithium bis(fluorosulfonyl)imide
[0281] The electrolytes of Examples 41 to 46 include any one of HS-320 (H), HSZ-360HUA, HSZ-660HOA, HSZ-385HUA, HSZ-980HOA and HSZ-390HUA as porous insulators (zeolites) having micropores, and EC as a medium and LiFSI as a metal salt disposed in the micropores, wherein the LiFSI as a metal salt is at least one selected from the group consisting of an alkali metal salt and an alkaline earth metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 41 to 46 are electrolytes included in the scope of the invention of claim 1.
[0282] In addition, the ionic conductivity of the electrolytes of Examples 41 to 46 was 1.1×10 -3 ~8.5×10 -3 S / cm increases with the increase of Si / Al ratio. This tendency indicates that the larger the Si / Al ratio, the more silanol groups exist on the inner wall of the micropores of the porous insulator. As a result, the carrier (Li + )’s jumping sites increase.
[0283] In addition, the ion conductivity of the electrolytes of Examples 41 to 46 (EC-LiFSi / zeolite system, molar ratio 0.3) was 1.1×10 -3 ~8.5×10 -3 On the other hand, the ionic conductivity of the electrolyte of Example 6 (EC-LiFSi / metal organic structure system, molar ratio 0.3) was 1.01×10 -3 S / cm. It can be seen from this that in a system where the porous insulator is zeolite, the ion conductivity can be further improved compared to a system where the metal organic structure is used.
[0284] <Examples 48 to 63: Alkali metal salt-medium / zeolite (HS-690) system>
[0285] The electrolytes of Examples 48 to 63 were prepared in the same manner as in Example 1, except that sulfolane (SL) as a medium was changed to a medium described in Table 8, LiSFI as a metal salt was changed to an alkali metal salt described in Table 8, and UiO-67 as a porous insulator was changed to zeolite (HS-690). The ion conductivity was measured. These results are shown in Table 8.
[0286] [Table 8]
[0287]
[0288] *1: Lithium bis(fluorosulfonyl)imide, *2: Bis(trifluoromethanesulfonyl)imide, *3: Lithium hexafluorophosphate,
[0289] *4: Lithium tetrafluoroborate, *5: Lithium perchlorate, *6: Propylene carbonate, *7: Vinylene carbonate, *8: Fluoroethylene carbonate, *9: Ethylene carbonate, *10: γ-butyrolactone, *11: 1,2-dimethoxyethane
[0290] The electrolytes of Examples 48 to 63 include HS-690 as a porous insulator (zeolite) having micropores, and any one of PC, VC, FEC, EC, GBL, diethylene glycol dimethyl ether and DME as a medium disposed in the micropores, and any one of LiFSI, LiTFSI, LiPF6, LiBF4 and LiClO4 as a metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 2.0 or less. That is, the electrolytes of Examples 48 to 63 are electrolytes included in the scope of the invention involved in claim 1.
[0291] <Examples 64 to 69: EC-LiFSI / mesoporous silica system>
[0292] The electrolytes of Examples 64 to 69 were prepared in the same manner as in Example 1, except that sulfolane (SL) as the medium was changed to the medium described in Table 9, and UiO-67 as the porous insulator was changed to the mesoporous silica described in Table 9, and the ion conductivity was measured. The results are shown in Table 9.
[0293] [Table 9]
[0294]
[0295] *1: Ethylene carbonate, *2: Lithium bis(fluorosulfonyl)imide
[0296] The electrolytes of Examples 64 to 69 include any one of MCM-48, SBA-15, MCM-41, and SBA-16 as porous insulators (mesoporous silica) having micropores, EC as a medium disposed in the micropores, and LiFSI as a metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 2.0 or less. That is, the electrolytes of Examples 64 to 69 are electrolytes included in the scope of the invention involved in claim 1.
[0297] In addition, the ion conductivity of the electrolytes of Examples 65 and 67 to 69 (EC-LiFSi / mesoporous silica system, molar ratio 0.5) was 3.1×10 -3 ~3.7×10 -3 On the other hand, the ionic conductivity of the electrolyte of Example 5 (EC-LiFSi / metal organic structure system, molar ratio 0.5) is 0.94×10 -3S / cm. It can be seen from this that in a system where the porous insulator is mesoporous silica, the ion conductivity can be further improved compared to a system where the porous insulator is a metal organic structure.
[0298] <Examples 71 to 80 and Comparative Example 10: SL-LiFSI / Zeolite System>
[0299] The electrolytes of Examples 71 to 80 were prepared in the same manner as in Example 1, except that UiO-67 as the porous insulator was changed to the zeolite described in Table 10, and the molar ratio (SL-LiFSI) was changed to the molar ratio described in Table 10. The ion conductivity was measured. The results are shown in Table 10.
[0300] [Table 10]
[0301]
[0302] *1: Sulfolane, *2: Lithium bis(fluorosulfonyl)imide
[0303] The electrolytes of Examples 71 to 80 include any one of HS-690, HS-642, HS-320 (Na), HSZ-980HOA and HSZ-840HOA as porous insulators (zeolites) having micropores, SL as a medium disposed in the micropores, and LiFSI as a metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is greater than 0.1 and less than 2.0. That is, the electrolytes of Examples 71 to 80 are electrolytes included in the scope of the invention involved in claim 1.
[0304] The ionic conductivity of the electrolytes of Examples 71 to 80 was 3.3×10 -4 ~42×10 -4 S / cm.
[0305] The electrolyte of Comparative Example 10 is an electrolyte not included in the scope of the invention of claim 1. Specifically, the molar ratio of the medium to the metal salt (medium / metal ratio) of the electrolyte of Comparative Example 10 exceeds 2.0. The ion conductivity of the electrolyte of Comparative Example 10 is 1.1×10 -4 S / cm.
[0306] Examples 71 to 80 included in the scope of the invention according to claim 1 have higher ion conductivity at room temperature than Comparative Example 10 not included in the scope of the invention according to claim 1 .
[0307] In addition, the integral value of the graph (not shown) showing the ionic conductivity of Examples 71 to 75 (SL-LiFSI / zeolite system, molar ratio 0.1 to 1.0) in Table 10 is greater than the integral value of the graph (not shown) showing the ionic conductivity of Examples 4 to 8 (SL-LiFSI / metal organic structure system, molar ratio 0.1 to 1.0) in Table 1. Figure 4 ) is the integral value. It can be seen that the electrolytes of Examples 71 to 75 exhibit higher ion conductivity than the electrolytes of Examples 4 to 8 (that is, the zeolite-based electrolyte has higher ion conductivity than the metal-organic structure-based electrolyte).
[0308] <Examples 81 to 87 and Comparative Example 11: SL-LiFSI / mesoporous silica system>
[0309] The electrolytes of Examples 81 to 87 and Comparative Example 11 were prepared in the same manner as in Example 1, except that UiO-67 as the porous insulator was changed to the mesoporous silica described in Table 11, and the molar ratio (SL / LiFSI) was changed to the molar ratio described in Table 11, and the ion conductivity was measured. These results are shown in Table 11.
[0310] [Table 11]
[0311]
[0312] *1: Sulfolane, *2: Lithium bis(fluorosulfonyl)imide
[0313] The electrolytes of Examples 81 to 87 include any one of MCM-48, SBA-15, MCM-41, and SBA-16 as porous insulators (mesoporous silica) having micropores, SL as a medium disposed in the micropores, and LiFSI as a metal salt, and the molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 2.0 or less. That is, the electrolytes of Examples 81 to 87 are electrolytes included in the scope of the invention involved in claim 1.
[0314] The ionic conductivity of the electrolytes of Examples 81 to 87 was 18×10 -4 ~120×10 -4 S / cm.
[0315] The electrolyte of Comparative Example 11 is an electrolyte not included in the scope of the invention of claim 1. Specifically, the molar ratio of the medium to the metal salt (medium / metal ratio) of the electrolyte of Comparative Example 11 exceeds 2.0. The ion conductivity of the electrolyte of Comparative Example 11 is 0.82×10 -4 S / cm.
[0316] Examples 81 to 87 included in the scope of the invention according to claim 1 have higher ion conductivity at room temperature than Comparative Example 11 not included in the scope of the invention according to claim 1 .
[0317] In addition, the integral value of the graph (not shown) showing the ionic conductivity of Examples 81 to 84 (SL-LiFSI / mesoporous silica system, molar ratio 0.2 to 1.0) in Table 11 is greater than the integral value of the graph (not shown) showing the ionic conductivity of Examples 4 to 7 (SL-LiFSI / metal organic structure system, molar ratio 0.2 to 1.0) in Table 1 Figure 4 ). It can be seen that the electrolytes of Examples 81 to 84 exhibit higher ion conductivity than the electrolytes of Examples 4 to 7 (i.e., the mesoporous silica electrolyte has higher ion conductivity than the metal organic electrolyte).
[0318] The electrolyte and battery according to the present disclosure are described below.
[0319] <1> An electrolyte having
[0320] Porous insulator having micropores, and
[0321] The medium and the metal salt are arranged in the micropores,
[0322] The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts,
[0323] The molar ratio of the medium to the metal salt (medium / metal salt) is 0.1 or more and 2.0 or less.
[0324] <2> The electrolyte according to <1>, wherein the medium is at least one of the following media:
[0325] A sulfonyl-based medium selected from the group consisting of sulfolane, dimethyl sulfone, 3-methyl sulfone and ethyl methyl sulfone;
[0326] A carbonate medium selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate and fluoroethylene carbonate;
[0327] A chain ether medium selected from the group consisting of 1,2-diethoxyethane and diethylene glycol dimethyl ether;
[0328] a lactone-based mediator selected from the group consisting of γ-butyrolactone and δ-valerolactone; and
[0329] A cyclic ether medium selected from the group consisting of 1,3-dioxolane and 1,3-dioxane.
[0330] <3> The electrolyte according to <1> or <2>, wherein the metal salt is a lithium salt.
[0331] <4> The electrolyte according to any one of <1> to <3>, wherein the porous insulator is at least one selected from the group consisting of metal organic structures, zeolites, and mesoporous silica.
[0332] <5> The electrolyte according to any one of <1> to <4>, wherein the positive ions constituting the metal salt are Li + , K + 、Na + or Mg 2+ .
[0333] <6> The electrolyte according to any one of <1> to <5>, wherein the negative ion constituting the metal salt is at least one selected from the group consisting of bis(fluorosulfonyl)imide ions, TFSI ions, tetrafluoroborate ions, and perchlorate ions.
[0334] <7> The electrolyte according to any one of <1> to <6>, which is a solid electrolyte.
[0335] <8> The electrolyte according to any one of <1> to <7>, wherein the medium is a sulfonyl-based medium having a sulfonyl group and at least one selected from the group consisting of sulfolane, dimethyl sulfone, 3-methyl sulfone, and ethyl methyl sulfone,
[0336] In the Raman spectrum, the peak derived from the SO2 angular vibration of the sulfonyl group is shifted to a higher wave number side.
[0337] <9> The electrolyte according to any one of <1> to <8>, wherein the negative ion constituting the metal salt is a bis(fluorosulfonyl)imide ion or a bis(trifluoromethanesulfonyl)imide ion,
[0338] In the Raman spectrum, the peak derived from the SNS stretching vibration of the negative ions constituting the metal salt is shifted to the high wave number side.
[0339] <10> The electrolyte according to any one of <1> to <9>, wherein the porous insulator is any one of zeolite and mesoporous silica.
[0340] <11> The electrolyte according to any one of <1> to <10>, wherein the porous insulator is any one of zeolite and mesoporous silica.
[0341] The Si / Al ratio of the zeolite and the mesoporous silica is 5.0 or more.
[0342] <12> The electrolyte according to any one of <1> to <11>, wherein the medium is at least one carbonate-based medium selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate.
[0343] <13> The electrolyte according to any one of <1> to <12>, wherein the medium is at least one carbonate-based medium selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate,
[0344] In the Raman spectrum, the peak derived from the breathing vibration of the heterocyclic ring contained in the carbonate-based medium is shifted to the high wave number side.
[0345] <14> A battery comprising the electrolyte according to any one of <1> to <13>.
[0346] Industrial Applicability
[0347] The battery including the electrolyte according to the present disclosure can be used in various fields where electricity storage is envisioned. Although only illustrative, batteries (especially secondary batteries) having the electrolyte involved in the present disclosure can be used in: electrical / information / communication fields using electrical / electronic equipment, etc. (for example, electrical / electronic equipment fields or mobile device fields including mobile phones, smart phones, laptops, digital cameras, activity meters, wristband computers, electronic paper, wearable devices, etc., RFID tags, card-type electronic money, smart watches and other small electronic devices); household / small industrial uses (for example, power tools, golf carts, household / nursing / industrial robots); large industrial uses (for example, forklifts, elevators, port cranes); transportation system fields (for example, hybrid vehicles, electric vehicles, buses, trams, electric assisted bicycles, electric motorcycles and other fields); power system uses (for example, various power generation, load regulators, smart grids, general household installation type storage systems and other fields); medical uses (medical equipment fields such as headphones and hearing aids); pharmaceutical uses (dose management systems and other fields); and IoT fields; space / deep sea uses (for example, space probes, submersible research vessels and other fields).
Claims
1. An electrolyte having Porous insulator having micropores, and The medium and the metal salt are arranged in the micropores, The metal salt is at least one selected from the group consisting of alkali metal salts and alkaline earth metal salts, The molar ratio of the medium to the metal salt, that is, medium / metal salt, is 0.1 or more and 2.0 or less.
2. The electrolyte according to claim 1, wherein The medium is at least one of the following: A sulfonyl-based medium selected from the group consisting of sulfolane, dimethyl sulfone, 3-methyl sulfone and ethyl methyl sulfone; A carbonate medium selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate and fluoroethylene carbonate; A chain ether medium selected from the group consisting of 1,2-diethoxyethane and diethylene glycol dimethyl ether; a lactone-based mediator selected from the group consisting of γ-butyrolactone and δ-valerolactone; and A cyclic ether medium selected from the group consisting of 1,3-dioxolane and 1,3-dioxane.
3. The electrolyte according to claim 1 or 2, wherein The metal salt is a lithium salt.
4. The electrolyte according to any one of claims 1 to 3, wherein The porous insulator is at least one selected from the group consisting of metal organic structures, zeolites, and mesoporous silica.
5. The electrolyte according to any one of claims 1 to 4, wherein The positive ion constituting the metal salt is Li + , K + 、Na + or Mg 2+ .
6. The electrolyte according to any one of claims 1 to 5, wherein The negative ion constituting the metal salt is at least one selected from the group consisting of a bis(fluorosulfonyl)imide ion, a bis(trifluoromethanesulfonyl)imide ion, a tetrafluoroborate ion, and a perchlorate ion.
7. The electrolyte according to any one of claims 1 to 6, The electrolyte is a solid electrolyte.
8. The electrolyte according to any one of claims 1 to 7, wherein The medium is a sulfonyl-based medium having a sulfonyl group and at least one selected from the group consisting of sulfolane, dimethyl sulfone, 3-methyl sulfone and ethyl methyl sulfone, In the Raman spectrum, the peak derived from the SO2 angular vibration of the sulfonyl group is shifted to a higher wave number side.
9. The electrolyte according to any one of claims 1 to 8, wherein The negative ion constituting the metal salt is a bis(fluorosulfonyl)imide ion or a bis(trifluoromethanesulfonyl)imide ion. In the Raman spectrum, the peak derived from the SNS stretching vibration of the negative ions constituting the metal salt is shifted to the high wave number side.
10. The electrolyte according to any one of claims 1 to 9, wherein The porous insulator is any one of zeolite and mesoporous silica.
11. The electrolyte according to any one of claims 1 to 10, wherein The porous insulator is any one of zeolite and mesoporous silica, The Si / Al ratio of the zeolite and the mesoporous silica is 5.0 or more.
12. The electrolyte according to any one of claims 1 to 11, wherein The medium is a carbonate-based medium selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate.
13. The electrolyte according to any one of claims 1 to 12, wherein The medium is at least one carbonate-based medium selected from the group consisting of ethylene carbonate, propylene carbonate, vinylene carbonate, and fluoroethylene carbonate, In the Raman spectrum, the peak derived from the breathing vibration of the heterocyclic ring contained in the carbonate-based medium is shifted to the high wave number side.
14. A battery, A method comprising providing the electrolyte according to any one of claims 1 to 13.
Citation Information
Patent Citations
Electrolyte regulator, its manufacturing method and use
JP2020508542A
